(3GdCfhGQ GdZQhjI aj TQM GddeYI GdOeTbjIs - (3GdHjGJj, GdfLaj, GdCMeOj, edG cJGH, eMeO LhGO Hf eMeO Jbj Hf eMeO, (B( (3cGf MjG (B1267 (3g` (B)s
(3ChdgG (B:s
(3GdMeO ddg (B... (3bGd GdeUfa bOS SQg cJGH GdML hajg aUhd GdML HaJM GdMGA hbO JcSQ dZI HeYfi GdbUO hgh CTgQ eYGfjg GddZhjI hEdjg jDhd eG Yf GdNdjd ef Cfg cKQI GdbUO Edi ef JYXeg hEf GNJdaG aj GdYehe hGdNUhU (B...s
(3BNQgG (B:s
... (3hCeQg HPdc hgh Chd Pj GdMLI hjhe JUOb HGdNGJe hgh GdQGHY hGdYTQjf ef Pj GdMLI hgh jhe GdeHGgdI hjhe fRhd gd CJi aj TCfg (B.. (3Je cJGH GdMLs
(3JHUQI GdYfhGf (B:s
(3hjSei CjVG H (B: (3GdeTcGI GdZQhjI TQM GddeYI GdOeTbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\201s
(3GdPQjYI (B2 - 243(1700)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis